Implementasi Scan Barcode Peminjaman Buku Perpustakaan Elektro Polnep berbasis ESP32 Dan Google Spreadsheets - Fitriansyah, Uday (Electrical Network Systems and Sources, 2025)
Libraries are media or institutions that act as library materials, in the form of written materials such as books, journals, and magazines. This media is used as a vehicle for education, research, and preservation of information that is arranged systematically with certain rules. Some libraries still use book borrowing and returning transactions in writing in books, one of which is the library of the Electrical Engineering Department of Pontianak State Polytechnic. This research is intended to simplify the transaction process in the library. The process of borrowing library books and reading membership uses a barcode scanner as input or sensor. Google spreadsheet is used as data storage received from the controller. The process that is passed is the process of data collection of books, the process of borrowing transactions and returning books.